A STUDY ON GOVERNANCE FRAMEWORK FOR AI AND ML SYSTEMS - Bhuvan, Seema (ShodhKosh: Journal of Visual and Performing Arts, 2023)
As artificial intelligence (AI) and machine learning (ML) systems increasingly permeate various sectors, establishing a robust governance framework becomes imperative to ensure ethical use, transparency, accountability, and security. This paper explores the critical components of a governance framework for AI and ML systems, highlighting the roles of policy, ethical guidelines, technical standards, and organizational practices. By examining existing frameworks and proposing a comprehensive model, this paper aims to provide a foundation for effective governance in the rapidly evolving field of AI and ML.